The Effect Of The Oryctes Rhinoceros Pest On Oil Palm Plants And How To Control It At PT Binanga Karya - Suleman, Andres; Rizal, Khairul; Sepriani, Yusmaidar; Harahap, Fitra Syawal (Jurnal Ragam Pengabdian, 2026)
This study aims to identify symptoms and attack levels of Oryctes rhinoceros, analyze its effect on vegetative growth, and evaluate integrated pest management strategies at PT Binanga Karya. A descriptive qualitative method was used, involving field observation, interviews, and documentation. Observations were conducted on 143 oil palm samples aged 30 months. Interviews were conducted with 2 foremen and 5 workers. Data analysis followed the Miles, Huberman & Saldana (2014) model. Results showed that 46.9% of sampled plants were attacked: light (19.6%), moderate (16.8%), and severe (10.5%). Symptoms included V-shaped boring holes, brown frass, broken spear leaves, and death of growing points. Moderate attack caused a 15-day delay per leaf and 20% reduction in stem height. Exacerbating factors included poor sanitation of decaying organic matter, high rainfall, and depression topography. PT Binanga Karya implemented IPM through routine sanitation, pheromone traps (1 unit/2 ha), manual larva collection, and targeted insecticide application. This integration reduced pest populations by over 70%. The study concludes that O. rhinoceros significantly affects vegetative growth of young oil palm, and the applied IPM strategy is effective in suppressing attacks.